2012
DOI: 10.1080/00981389.2012.659837
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Families of Children With Special Health Care Needs for Disasters: An Education Intervention

Abstract: Children with special health care needs pose a special challenge in post-disaster response. Current research suggests that the general population is not adequately prepared for a major disaster event, with members of vulnerable populations even less prepared. The purpose of this study was to determine the short-term effectiveness of a brief patient education intervention aimed at increasing levels of disaster preparedness among families of special health care needs children. One hundred twenty-one families wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…Our results indicate that like much of the general public, 3 parents of children with DD were under-prepared for emergencies, both by self-report of their general state of preparedness and by number of preparedness steps taken. These findings are consistent with those of Baker and colleagues, 3,37 who found that parents of children with SHCN were generally unprepared in terms of supplies, planning, and knowledge. Baker and colleagues’ findings suggest no differences in preparedness levels between parents whose children had a single special need and those whose children had more than one special need.…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicate that like much of the general public, 3 parents of children with DD were under-prepared for emergencies, both by self-report of their general state of preparedness and by number of preparedness steps taken. These findings are consistent with those of Baker and colleagues, 3,37 who found that parents of children with SHCN were generally unprepared in terms of supplies, planning, and knowledge. Baker and colleagues’ findings suggest no differences in preparedness levels between parents whose children had a single special need and those whose children had more than one special need.…”
Section: Discussionsupporting
confidence: 91%
“…Children with disabilities, who may already have limited social networks, are often separated from caregivers during a disaster. This deprives the children of critical information and support, and disrupts the continuity of medical care (Baker et al 2012).…”
Section: Children With Disabilities and Their Experiences Of Disastersmentioning
confidence: 99%
“…Recent disasters have revealed complexities in the associated responses when considering the needs of potentially vulnerable populations (Redlener 2008;Baker et al 2012).…”
Section: Obstacles To Involving Children With Disabilities In Disastementioning
confidence: 99%
“…The limited literature on use of EIFs in CMC includes consensus statements by academies and medical societies specifying contents of EIFs and advocating their use, 1,2 surveys of parents and practitioners, 16,26 as well as attempts to educate families 29 and implement EIFs in selected patient populations. 20,21,30 There is strong consensus among the pediatric and emergency medicine medical societies that CMC are a vulnerable patient population that requires critical information to be readily available to health care providers for delivery of optimal care during emergencies.…”
Section: Discussionmentioning
confidence: 99%